EVALUASI PENJADWALAN DAN PENGENDALIAN WAKTU MENGGUNAKAN METODE PRECEDENCE DIAGRAM METHOD (PDM): Studi Kasus: Proyek Pembangunan Gedung Kantor Pabrik PT. Macropima Panganutama Semarang - Andriansyah, Muhamad Yunus; Maskur, Atep; Hartati, Gini (Jurnal Ilmiah Teknik Sipil, 2026)
One of the scheduling methods often used in project scheduling is the Precedence Diagram Method. This construction project experienced a delay in duration from the initial plan of 148 days to 162 days. The objective of this study is to determine the results of time scheduling calculations using the Microsoft Project-based Precedence Diagram Method method and to compile a Precedence Diagram Method network diagram in the Evaluation of Scheduling and Control in the Construction of the PT. Macroprima Panganutama Semarang Factory Office Building. The research method used is a descriptive method with a quantitative approach. Based on the Precedence Diagram Method method calculation results using Microsoft Project, the critical path is in the pile cap works for the RCBK building, concrete slab works, steel structure column works, steel structure beam works, steel structure roof accessory works, and iron works, with a total project completion duration of 120 days. To achieve this 120-day duration, overtime work is added three times a week, carried out every Tuesday, Thursday, and Friday. Overtime work hours are from 4:00 p.m. to 10:00 p.m. Another alternative is to accelerate the duration (crashing) by adding three workers, two craftsmen, and one steel craftsman to crash every task on the critical path, resulting in 135 days. According to field data, this project was completed in 162 days, while the project plan was 148 days. In this case, project scheduling using the Precedence Diagram Method method with Microsoft Project is the fastest and most optimal because the project can be scheduled and completed in 120 days.